Potential for combined delivery of riboflavin and all-trans retinoic acid, from silk fibroin for corneal bioengineering. - Ahearne, Mark (My University, 2019)
Millions of people worldwide suffer from vision impairing conditions resulting from corneal injury or disease. Silk fibroin (SF) is an emerging biopolymer that has been used for several applications including the fabrication of bioengineered corneas and ocular prostheses. To improve the cell response to SF, riboflavin (RF) and all-trans retinoic acid (RA) were coupled onto SF matrices. RF is a photo-initiator that has previously been combined with ultraviolet light to crosslink corneal collagen while RA has been used to regulate the phenotype of corneal stromal cells and their extracellular matrix deposition. Different concentrations of RF and RA were respectively photo-crosslinked and covalently bound through carbodiimide coupling onto 2% SF matrices. The effect of incorporating these molecules on the physical, chemical and mechanical properties of the matrices was evaluated. The biological response of human corneal stromal cells to the matrices was examined using cellular adhesion assays, proliferation assays, cytoskeleton staining, gene expression analysis and immunocytochemical staining. RF and RA both led to changes in the surface nanostructure and hydrophilicity while just RF increased the material stiffness. Cells cultured on the matrices containing both biomolecules displayed improved cellular proliferation, increased GAG deposition and increased expression of keratocyte genes that are normally associated with healthy corneal stromal tissue. These in vitro studies serve as a starting point for the optimization of loading bioactive molecules on SF based matrices for formulating clinically relevant ocular implants.
PUBLISHED
Keywords: Retinoic acid; Cornea; Fibroin; Regeneration; Riboflavin; Stroma